Frontier insect pest management technologies for sustainable rice production - Seni, Atanu (Journal of Cereal Research, 2021)
Although effective management of rice insect-pests can be achieved by insecticides but their excessive long term use poses human health and environmental risks in addition to effect on non-targets organisms. Now-a-days, some pest management practices such as agronomic practices like smart fertilizer and nutrient application, real time monitoring and surveillance, ecological engineering through habitat manipulation, biological control by more effective strain, nanotechnology, host plant resistance by RNAi and marker assisted selection, have been introduced and adopted to manage rice insect pests which are eco-friendly in nature and also promote natural pest management. Here, this article intended to discuss the various frontier pest management technologies which will help for sustainable rice production.